Thermal State Entanglement Entropy on a Quantum Graph - Elias-Moreno, R (American Physical Society, 2019)
A particle jumps between the nodes of a graph interacting with local spins. We show that the entanglement entropy of the particle with the spin network is related to the length of the minimum cycle basis. The structure of the thermal state is reminiscent of the string net of spin liquids. © 2019 American Physical Society.